A Cross-Sectional Study on the Quality of Life in Women with Endometrioma - Thammasiri C; Amnatbuddee S; Sothornwit J; Temtanakitpaisan T; Buppasiri P (Dove Medical Press, 2022)
Chutikarn Thammasiri, Siriruthai Amnatbuddee, Jen Sothornwit, Teerayut Temtanakitpaisan, Pranom Buppasiri Department of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, ThailandCorrespondence: Siriruthai AmnatbuddeeDepartment of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, 123 Mittraphap Road, Muang District, Khon Kaen, 40002, ThailandTel +66817396331Email siriruthai@kku.ac.thPurpose: To evaluate the quality of life (QoL) of women with endometrioma and explore the associated factors.Patients and Methods: A cross-sectional study was conducted between August 2020 and March 2021. A total of 99 women diagnosed with ovarian endometrioma with at least one endometriosis-associated symptom completed the Endometriosis Health Profile 30 (EHP-30) questionnaire for their QoL score before treatment for ovarian endometrioma. The questionnaire comprises a central questionnaire (30 items) and a modular questionnaire (23 items divided into 6 sections). Demographics and QoL scores were analyzed using descriptive statistics and multivariable linear regression or median regression.Results: The mean QoL score was 35.0± 15.8 (range, 16.0± 21.2 in the social support dimension to 45.1± 24.4 in the control and powerlessness dimension). In the modular questionnaire, the highest score was in the infertility domain, while the lowest was in the relationship with the physician domain. The pain score and chronic pelvic pain (CPP) were independent correlation factors for a higher total EHP-30 score: the higher the total EHP-30, the poorer the QoL. CPP was positively correlated with the QoL score in the work domain.Conclusion: The present study revealed that CPP was the factor associated with a worse QoL and work performance in women with endometrioma based on a disease-specific, EHP-30 questionnaire.Keywords: endometriosis, pelvic pain, infertility, EHP-30